2013
DOI: 10.3109/02713683.2013.783078
|View full text |Cite
|
Sign up to set email alerts
|

Minor Influence of Sub-Bowman Keratomileusis on the Posterior Corneal Surface at Early Stage

Abstract: The posterior corneal surface showed central flattening and peripheral steepening at early stage post-SBK. To combine the asphericity with the elevation of the posterior corneal surface can overall and accurately understand the posterior corneal shape and its variations after refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
5
9
0
Order By: Relevance
“…It may be easy to believe that ΔPCE or ΔPME was correlated with residual stromal thickness (RST) or AD, as Zhao et al [9] reported that RST was correlated with ΔPCE in their high-myopia group post SMILE, while in the current study, neither ΔPCE nor ΔPME had a significant correlation with RST, which is in accordance with previous studies [4,6,[21][22][23]. The contradiction may be caused by the different degrees of myopia corrected in surgery.…”
Section: Discussionsupporting
confidence: 88%
“…It may be easy to believe that ΔPCE or ΔPME was correlated with residual stromal thickness (RST) or AD, as Zhao et al [9] reported that RST was correlated with ΔPCE in their high-myopia group post SMILE, while in the current study, neither ΔPCE nor ΔPME had a significant correlation with RST, which is in accordance with previous studies [4,6,[21][22][23]. The contradiction may be caused by the different degrees of myopia corrected in surgery.…”
Section: Discussionsupporting
confidence: 88%
“…() inferred that peripheral steepening and central flattening of the posterior corneal surface at early‐stage operative eyes (Yan et al. ), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The negative value is greater, the cornea is more prolate (Read et al 2006;Calossi 2007;Gonzalez-Meijome et al 2007). Our data demonstrated that the mean Qvalue of LASIK eyes changed into a positive direction compared to (Yan et al 2013), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…With posterior corneal forward displacement proved to be an important warning sign of postoperative corneal instability, posterior corneal elevation has long been adopted in evaluating corneal displacement after nearly all keratorefractive surgeries including PRK [ 18 ], laser assisted subepithelial keratomileusis (LASEK), sub-Bowman’s keratomileusis (SBK) [ 19 ], LASIK [ 20 ] and SMILE [ 21 ].…”
Section: Discussionmentioning
confidence: 99%